2013
DOI: 10.1177/1077695812472895
|View full text |Cite
|
Sign up to set email alerts
|

Scholastic Journalism Teacher Use of Digital Devices and Social Networking Tools in a Poor, Largely Rural State

Abstract: Research showing adolescents' ever-increasing use of digital devices, combined with calls from governmental officials to incorporate more technology into classroom activities, prompted this survey of Arkansas scholastic journalism advisers. The goal was to determine how they used digital communication devices in their teaching. Results showed lack of funding, lack of teacher experience, and lack of administrative permission suppressed use of several devices, while student-owned devices were used for a variety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…While it incorporates most—if not all—of the “core skills” assessed on these tests, journalism is not, and likely never will be, a core skill. Studies with relatively small samples and/or case studies give indications that journalism participation can foster greater civic knowledge, engagement, and pride (Clark & Monserrate, 2011; Marchi, 2012; Neely, 2015; Tuggle, Sneed, & Wulfemeyer, 1999) and build technology self-efficacy, particularly in lower SES students (Plopper & Conaway, 2013). Applying self-determination and occupational theories in this study of a large data set hints at the possibility of effects on concepts such as motivation, autonomy, and eventual job satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…While it incorporates most—if not all—of the “core skills” assessed on these tests, journalism is not, and likely never will be, a core skill. Studies with relatively small samples and/or case studies give indications that journalism participation can foster greater civic knowledge, engagement, and pride (Clark & Monserrate, 2011; Marchi, 2012; Neely, 2015; Tuggle, Sneed, & Wulfemeyer, 1999) and build technology self-efficacy, particularly in lower SES students (Plopper & Conaway, 2013). Applying self-determination and occupational theories in this study of a large data set hints at the possibility of effects on concepts such as motivation, autonomy, and eventual job satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Local news coverage is particularly important to assess in rural newspapers, as it will help to understand the role of gender in these communities and thus the context of gender and power relations in which IPV occurs in those locations. Community newspaper readership remains high in Iowa communities (INA, 2013), and research has indicated that rural areas of the United States also use the Internet and social media sites frequently to access media information (Han, LaRose, Steinfield, & Velasquez, 2011;Plopper & Conaway, 2013). This is worth noting in this study because although many people subscribe to the rural community newspapers, the newspapers' reach expands beyond subscribers because nonsubscribers are still able to access this information from the websites or Facebook pages of those newspapers that have them.…”
Section: Content Analysismentioning
confidence: 99%